The nineteenth-century struggle to preserve Irish culture in the context of cultural security - Biernat, Marcin (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
This review article focuses on the issue of internal security and cultural identity, using Ireland as an example. National and cultural identity contribute to social cohesion and can also influence social stability. The analysis of the struggle to protect Irish identity during turbulent times illustrates the important role of collective identity in maintaining cohesion within society and thus ensuring internal security. The idea of cultural security is central to the preservation of culture. The theme is analyzed in terms of various initiatives in nineteenth-century Ireland aimed at preserving tradition, culture and Irishness